Inovasi Perpustakaan Melalui Pemanfaatan Teknologi Augmented Reality Dan Virtual Reality di Era Generasi Z - Aulianto, Dwi Ridho (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2020)
This study aims to determine the benefits of Augmented Reality and Virtual Reality technology applied to libraries in the Z generation era. The research method used study of literature by collecting several reference as sources that are relevant to the study material and and interviews with several generation Z informants. The results of the study found that the implementation of Augmented Reality technology can be used to create and read the Interactive Opac Brochure with AR; Utilization of Library Collection Display; Utilization for Searching Library Collections in Shelves through AR; Utilization for Interactive Learning Media for Users. While the implementation of Virtual Reality technology can be used for tours or library tours; Library Services; Information Literacy and Online Catalog.